Academic procrastination as a self-regulatory failure: the combined influence of academic stress and fear of failure - Dimas Ibrahim Salam; Halim Purnomo; Abdul Madjid; Azam Syukur Rahmatullah (Indonesian Institute For Counseling, Education and Therapy, 2026)
Academic procrastination remains a prevalent issue among university students and has been associated with adverse academic outcomes, including reduced academic performance, poor self-regulation, and increased psychological distress. Although procrastination is often attributed to ineffective time management, growing evidence suggests that underlying psychological factors may play a more substantial role in shaping students’ delaying behaviors. This study investigated the extent to which academic stress and fear of failure predict academic procrastination among undergraduate students. A quantitative cross-sectional design was employed, and data were collected through self-report questionnaires administered to undergraduate students. The data were analyzed using multiple linear regression to examine the predictive contributions of academic stress and fear of failure to academic procrastination. The findings revealed that academic stress significantly and positively predicted academic procrastination, indicating that students experiencing higher levels of academic stress were more likely to delay academic tasks. Fear of failure was also found to be a significant positive predictor of academic procrastination. Furthermore, the regression model demonstrated that academic stress and fear of failure jointly contributed to explaining variations in procrastination behavior. These findings suggest that academic procrastination is influenced not only by behavioral factors but also by psychological vulnerabilities related to stress and failure concerns. Therefore, interventions aimed at reducing academic procrastination should incorporate strategies for stress management and addressing maladaptive fear of failure to enhance students’ academic functioning and self-regulatory capacities.